Analysis of the Meaning Structure in the Lyrics of the Bugis Song “Bunga Ripalla”: A Saussurean Semiotic Study - Abdul Rauuf Muri; Sumarlin Rengko HR (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the meaning structure constructed in the lyrics of the Bugis song Bunga Ripalla by H. Mustafa Bande using a Saussurean semiotic framework. Although regional song lyrics in Indonesia have been examined from linguistic and cultural perspectives, detailed structural semiotic analyses of traditional Bugis songs remain limited. Addressing this gap, the present research applies a descriptive qualitative design with lyric lines as units of analysis. Data were derived from an authoritative and widely circulated version of the song, verified through cultural informant consultation. The analysis operationalizes Saussure’s signifier–signified model to identify symbolic patterns and relational meaning structures. The findings reveal four dominant symbolic clusters: (1) elevation imagery (mountain/height) representing idealized expectation, (2) flight imagery (bird/wings) symbolizing striving beyond limitation, (3) boundary imagery (sky edge/path) signifying obstruction, and (4) floral imagery (fenced flower) representing restricted love. These interrelated signs construct a coherent emotional progression from idealization to disappointment and reflective acceptance. The study demonstrates that Bunga Ripalla constructs a unified emotional narrative through culturally grounded signifier–signified relations that reflect Bugis perspectives on love, aspiration, and social limitation. The research contributes to semiotic theory application in regional literature and expands scholarly attention to Bugis cultural texts.